Control of seed weight by a DNA demethylase in soybean - Mengzhu Zhang; Wu Jiao; Xinyu Jiang; Jinhui Wang; Longfei Wang; Wenxue Ye; Yue Wang; Qingshan Chen; Dawei Xin; Qingxin Song (Crop Design)
Soybean seeds are a major source of protein and oil for human and animal nutrition. The molecular mechanisms underlying seed weight regulation, especially through epigenetic processes, are still poorly understood in soybean. Here, we reveal that a DNA demethylase gene, GmDMEa, underlies a genetic locus controlling seed weight through genome-wide association studies of 316 soybean accessions. Disruption of GmDMEa by CRISPR/Cas9 significantly increases seed weight and yield per plant accompanied with increased DNA methylation levels in the specific genomic regions which are demethylated in endosperm relative to embryo. GmDMEa is involved in activation of the endosperm-preferred genes that are negatively correlated with seed weight. Furthermore, DNA methylation variations induce significant changes of chromatin accessibility in endosperm. Notably, allelic variations of GmDMEa were artificially selected during soybean domestication. These findings reveal the role of dynamic DNA methylation in regulation of seed weight and provide a valuable gene resource for soybean breeding.